Systematic Literature Review on the Efficacy of MRI in Musculoskeletal Disorder - Helmin Rumbiak; Budiman, M Arif; Dewanto (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study focuses on the Systematic Literature Review (SLR) regarding the efficacy of the use of Magnetic Resonance Imaging (MRI) in diagnosing and assessing musculoskeletal disorders. The methodology used involves collecting and analyzing data from various previously published studies. Strict inclusion criteria are applied to ensure the relevance and quality of the reviewed studies. Out of a total of 120 articles identified, 10 articles met the criteria and were included in the analysis. The results of the SLR show that MRI is a highly effective diagnostic tool, providing a detailed picture of bone structure, soft tissue, and cartilage without the need for radiation exposure. The study also found that MRI has high sensitivity and specificity in identifying various types of musculoskeletal disorders, including but not limited to arthritis, ligament injuries, and tendon ruptures. What's more, MRI supports early diagnosis which helps in designing a precise and personalized treatment plan, potentially reducing the patient's recovery time. From this analysis, we recommend a wider use of MRI in musculoskeletal clinical practice. However, more research is needed to optimize the protocol and reduce the associated costs, thereby expanding its accessibility across various medical settings.